Artemisinin antimalarials in pregnancy: a prospective treatment study of 539 episodes of multidrug-resistant Plasmodium falciparum. - Mcgready, R; Cho, T; Keo, N; Thwai, K; Villegas, L; Looareesuwan, S; White, N; Nosten, F (2001)
The emergence and spread of multidrug-resistant Plasmodium falciparum compromises the treatment of malaria, especially during pregnancy, where the choice of antimalarials is already limited. Artesunate (n=528) or artemether (n=11) was used to treat 539 episodes of acute P. falciparum malaria in 461 pregnant women, including 44 first-trimester episodes. Most patients (310 [57.5%]) received re-treatments after earlier treatment with quinine or mefloquine. By use of survival analysis, the cumulative artemisinin failure rate for primary infections was 6.6% (95% confidence interval, 1.0-12.3), compared with the re-treatment failure rate of 21.7% (95% confidence interval, 15.4-28.0; P=.004). The artemisinins were well tolerated with no evidence of adverse effects. Birth outcomes did not differ significantly to community rates for abortion, stillbirth, congenital abnormality, and mean gestation at delivery. These results are reassuring, but further information about the safety of these valuable antimalarials in pregnancy is needed.